Poeci czasu Soboru: Wojtyła, Twardowski, Pasierb - SOCHOŃ, Jan (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
The article presents three artistic strategies inspired by the event of Second Vatican Council and applied in the poetry of, respectively, Karol Wojtyła (Pope John Paul II), Fr. Jan Twardowski, and Fr. Janusz Pasierb. One may rightly claim that had it not been for Pope John XXIII’s decision to convene the Council, their poetic work would have followed a different direction. While the three poets certainly differed in their approach to poetry as such, what they shared was that each of them pursued his own personal project of poetic theology, its center being man. Each of them, in his poems, referred to the new situation of the human being in the modern world, with its preference of liberal attitudes, the prevailing license of opinion, religious indifference, growing distance from the Church and tradition, and its abandonment of the conduct described in the Gospels. Wojtyła, as well as Twardowski and Pasierb, perceived the remedy for this situation in the new vision of the reality provided by the Council. The core of that vision was that the people of modern times, whether they believe in God or do not recognize him explicitly, should perceive clearly the integrity of their vocation and, having adopted the attitude of love, act in order that human dignity is respected and the brotherhood of all human beings deepened. The attitude of love was considered by the three poets as the only possibility to respond to the burning issues of the new age. The poetic sensibilities of Wojtyła (John Paul II), Twardowski and Pasierb opened the Church onto original poetic voices and lyrical emotions. Their accomplishment is still alive in the ongoing process of building a world in which God, man and culture, the fruit man’s effort, constitute a unity. In the name of the highest good, this unity needs to be constantly deepened and reinforced.